D-section Tissue cutter – a new grossing tool: An observational study (Journal of Pharmaceutical Negative Results, 2022)
Background: Grossing is the process of selecting, cutting, and orienting individually labelled specimens, recording the number and macroscopic description of tissues kept for processing.Aim: The aim of the study is to compare the efficiency of our invention, D-section Tissue cutter and scalpel with Bard Parker blade No: 11.Materials And Methods: 20 formalin fixed tissues from 5 different sites were retrieved from the tissue storage of the Department of Oral and Maxillofacial Pathology. Tissues retrieved were oral mucosa, tongue, skin, lymph node and decalcified bone. The size of the tissue was from 1 to 3 cm. The tissues were cut using the D Section Tissue cutter and Scalpel. Two investigators analysed the efficiency of the instrument on each tissue type on the quality parameters including borders, cutting efficiency, depth of sectioning, difficulty in stability of specimen and time taken for cutting.Results: Good Stabilisation of the specimen and clean cut borders were found in lymph node samples using a D section tissue cutter. Precise cutting edge of tissues was found in adipose tissue when compared to BP blades. No significant difference was found on comparing D section tissue cutter and BP blades.Conclusion: D-section tissue cutter showed superior results when compared to BP blade. This instrument is safe to use, easy to transport, precision and accurately cuts the tissue.